2017
DOI: 10.3835/plantgenome2016.07.0071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity and Host Resistance to Stem Rust in USDA NSGC Durum Wheat Accessions

Abstract: The USDA-ARS National Small Grains Collection (NSGC) maintains germplasm representing global diversity of small grains and their wild relatives. To evaluate the utility of the NSGC durum wheat (Triticum turgidum L. ssp. durum) accessions, we assessed genetic diversity and linkage disequilibrium (LD) patterns in a durum core subset containing 429 lines with spring growth habit originating from 64 countries worldwide. Genetic diversity estimated using wheat single-nucleotide polymorphism (SNP) markers showed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 87 publications
1
46
0
Order By: Relevance
“…Population structure might bring false positive or negative marker-trait associations (MTAs) which should be considered as covariates in GWAS analysis. The population structure of the durum wheat panel based on the full set of informative SNPs has been previously described (Aoun et al, 2016; Chao et al, 2017). Due to the possible impact of linkage on the inference of genetic relationships, the genetic stratification issue was revisited by running an analysis using a sub-set of unlinked markers (pairwise LD < 0.2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Population structure might bring false positive or negative marker-trait associations (MTAs) which should be considered as covariates in GWAS analysis. The population structure of the durum wheat panel based on the full set of informative SNPs has been previously described (Aoun et al, 2016; Chao et al, 2017). Due to the possible impact of linkage on the inference of genetic relationships, the genetic stratification issue was revisited by running an analysis using a sub-set of unlinked markers (pairwise LD < 0.2).…”
Section: Resultsmentioning
confidence: 99%
“…The line information and genotype data of the 493 durum wheat entries were reserved in the T3/Wheat database 2 . This panel has previously been exploited to identify the genetic basis of resistance against certain foliar pathogens (Aoun et al, 2016; Chao et al, 2017). In addition, genotypic data from a domesticated emmer wheat (Sun, 2015) and a bread wheat (Cavanagh et al, 2013) diversity panel was used to infer the genetic divergence of identified quantitative trait loci (QTL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though several studies have evaluated seedling and/or field response of wheat association mapping panels to Pgt isolates (Yu et al, 2011 , 2012 ; Letta et al, 2014 ; Zhang et al, 2014 ; Gao et al, 2017 ; Mihalyov et al, 2017 ; Muleta et al, 2017 ), only one has evaluated field response of the wheat population studied to more than one Pgt race (Chao et al, 2017 ). In that study, field response of a bulk of six Pgt isolates in Minnesota was compared to response to a bulk of Pgt isolates in Ethiopia, and differences between these datasets could be due to environment and/or race.…”
Section: Discussionmentioning
confidence: 99%